PEMBERDAYAAN EKONOMI MASYARAKAT DENGAN MENGANGKAT USAHA BATIK KHAS BAKARAN KABUPATEN PATI - Akhmad Nurrofi; Nuruddin Mahmud; Bayu Teguh Wibowo (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
The aim of community service is to provide knowledge and motivation to pertners so they can mange micro, small and medium enterprises better. The focus on human resource management and environmental cleliness is expected to improve creativity, product peckaging and marketing. The results of the training include increasing partners’ understanding of entrepreneurship concept. The training was successful in increasing partners end knowledge in business management, and was able to have a positive impach on partners, tutors, institusiam and knowledge in business management. And was able to have a positive impact on partners, tutors, institutions and local community, as well as encouraging the development of hand written batik MSMEs. In Pati Regency